Answer:
Step-by-step explanation: (8a + 2b + -4) = (3b + -5)
Reorder the terms:
(-4 + 8a + 2b) = (3b + -5)
Remove parenthesis around (-4 + 8a + 2b)
-4 + 8a + 2b = (3b + -5)
Reorder the terms:
-4 + 8a + 2b = (-5 + 3b)
Remove parenthesis around (-5 + 3b)
-4 + 8a + 2b = -5 + 3b
Solving
-4 + 8a + 2b = -5 + 3b
Solving for variable 'a'.
Move all terms containing a to the left, all other terms to the right.
Add '4' to each side of the equation.
-4 + 8a + 4 + 2b = -5 + 4 + 3b
Reorder the terms:
-4 + 4 + 8a + 2b = -5 + 4 + 3b
Combine like terms: -4 + 4 = 0
0 + 8a + 2b = -5 + 4 + 3b
8a + 2b = -5 + 4 + 3b
Combine like terms: -5 + 4 = -1
8a + 2b = -1 + 3b
Add '-2b' to each side of the equation.
8a + 2b + -2b = -1 + 3b + -2b
Combine like terms: 2b + -2b = 0
8a + 0 = -1 + 3b + -2b
8a = -1 + 3b + -2b
Combine like terms: 3b + -2b = 1b
8a = -1 + 1b
Divide each side by '8'.
a = -0.125 + 0.125b
Simplifying
a = -0.125 + 0.125b